2016
DOI: 10.1111/ejn.13257
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐Interleukin 1 Receptor domain‐containing adaptor protein positively regulates BV2 cell M1 polarization

Abstract: Microglial activation, including classical (M1) and alternative (M2) activation, plays important roles in the development of several central nervous system disorders and promotes tissue reconstruction. Toll-like receptor (TLR)4 is important for microglial polarization. TIR domain-containing adaptor protein (TIRAP) is an intracellular adaptor protein, which is responsible for the early phase of TLR4 activation. The role of TIRAP in BV2 cell M1 polarization is still unknown. In this study, we showed that TIRAP e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Increased expression of CD86, a known M1 receptor marker (Gong et al, 2016) was found in the cortex and striatum of 5xFAD mice, and in Aβ-treated BV2 microglia. Based on our results, we suggest that adiponectin might promote the polarization of M2 type microglia under Aβ toxicity conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Increased expression of CD86, a known M1 receptor marker (Gong et al, 2016) was found in the cortex and striatum of 5xFAD mice, and in Aβ-treated BV2 microglia. Based on our results, we suggest that adiponectin might promote the polarization of M2 type microglia under Aβ toxicity conditions.…”
Section: Discussionmentioning
confidence: 97%
“…The cells were incubated with the primary antibodies overnight at 4°C. The primary antibody anti-rabbit CD86 (1:500, Cell Signaling) as a marker of M1 phenotype microglia (Gong et al, 2016) was used. After incubation, BV2 cells were washed twice with PBS and incubated with specific secondary antibody for 1 h 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The deletion of TLR4 improves ICH outcomes via inhibition of the NF-κB signaling pathway in the blood-injection ICH model (Lively and Schlichter, 2012). Furthermore, TLR4 activation has been shown to be essential for M1 microglial polarization in glioma stem cells in vivo (a Dzaye et al, 2016) and in BV-2 cells in vitro (Gong et al, 2016; Wang et al, 2016). Our data show that pinocembrin decreases M1 phenotype micro-glia, as evidenced by decreases in the number of the CD16/32 + microglia and iNOS expression in MACS-sorted CD11b + microglia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not characterize the exact microglial phenotype (classically activated or alternatively activated) that is modulated by ATX after SAH. Previous studies reported that TLR4 activation is essential for polarization to the classically activated phenotype in vivo and in vitro (16,71,72). We therefore speculate that ATX might inhibit classic activation by inhibiting TLR4.…”
Section: Discussionmentioning
confidence: 65%